Accident and evolution - Соловйов, В. О. (Man and Environment. Issues of Neoecology, 2014)
Correlation of the concepts and evolution of disasters, which have been subject of lengthy debate. It’s not mutually exclusive, they are usually interpreted as vzaimosvyazannyae a phenomenon in which the expression of catastrophes accelerates the evolutionary development.